Sewage disposal and arboviruses in Brazil - Luciano Pamplona de Góes Cavalcanti; Artur Timerman (Rev Rene)
It is known that the actions intended to expand the sewage disposal coverage and the access to drinking water have an impact on people’s health. Nevertheless, what is the possible association between these actions and the decrease in vector-borne diseases? In Brazil, sewage disposal has advanced significantly in the last few years, but it is not enough. One of the Millennium Development Goals, with respect to ensuring environmental sustainability, was to reduce the proportion of people without sustainable access to water and sewer. Part of this goal was achieved by Brazil, when it expanded the percentage of the population with public network water supply from 70.0%, in 1990, to 85.5%, in 2012. However, this percentage is not homogeneous and there is a considerable discrepancy among the different regions of the country.